Pengembangan Jobsheet Media Trainer Sistem Kelistrikan Toyota Kijang 4K - Dede Rachmad; Irma Yulia Basri; Andrizal Andrizal (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2021)
This study aims to develop job sheets on the subject of electrical maintenance of light vehicles. The type of research used is Research and Development (R&D) with a 4-D model development procedure. This research consists of four stages, namely: Define, Design, Develop, and Disseminate. The subjects used were students of SMK N 5 Padang, the data analysis technique used was technical analysis from the experts by looking at the validity and practicality of the jobsheet. The results showed that the jobsheet met the principle of relevance in the qualifications for learning materials from the expert's assessment with a level of 0.921 stated in the valid category. Based on the teacher's response with a value of 90.67%, it is stated that it is practical. Based on the development of this jobsheet, it can be concluded that the jobsheet is valid and practical and for learning in schools.